SUPERHEATED STEAM GENERATOR - NAGAHATA HIROSHI (2016)
PROBLEM TO BE SOLVED: To provide a superheated steam generator capable of improving energy efficiency by generating high temperature steam capable of being utilized in a desired appliance and treatment process, by waste heat such as exhaust heat recovered from an air fin cooler.SOLUTION: Circulated saturation water is heated by a first heat exchanger 22 by using waste heat disposed of from an appliance such as an air fin cooler 21, and steam sucked from a first evaporation can 23 by a first vacuum pump 25 is supplied to a second heat exchanger 31. To the second heat exchanger, water of boiling point is introduced from a second evaporation can 32 to be heated, and then returned to the second evaporation can 32, the steam generated in the second evaporation can 32 is sucked by the second vacuum pump 33, and distributed while branched to a blower 34 and a third heat exchanger 35. The steam is supplied to a desired appliance and the like from the blower 34, the boiler supply water introduced from a water supply pipe 36 is heated by the third heat exchanger 35, and the boiler supply water and the steam are mixed and returned to the second evaporation can 32.SELECTED DRAWING: Figure 1 【課題】 回収したエアフィンクーラーからの排気熱等の廃熱により、所望の設備や処理工程に利用できる高温蒸気を発生させることで、エネルギー効率の向上を図る過熱水蒸気発生器を提供する。【解決手段】 エアフィンクーラー21等の設備から廃棄される廃熱を第１熱交換器22により循環飽和水を加熱し、第１蒸発缶23から第１真空ポンプ25で吸引されて水蒸気が第２熱交換器31に供給される。第２熱交換器には第２蒸発缶32から沸点水が導入されて加熱された後、第２蒸発缶32に返戻され、第２蒸発缶32内で発生した水蒸気が第２真空ポンプ33で吸引されて、ブロワー34と第３熱交換器35とに分岐させて送られる。ブロワー34から所望の設備等に供給され、第３熱交換器35で給水管36から導入されるボイラー給水を加熱した後、該ボイラー給水を混合させて第２蒸発缶32に返戻される。【選択図】 図１